Reflexões no processo ensino / aprendizagem e suas implicações na formação inicial docente: contextos inclusivos na Educação de Jovens e Adultos - Enviy, Perla Cristiane (2019)
The objective of this research is to analyze aspects of the initial teaching formation, from pedagogical practices developed in the Supervised Internship discipline in the EJA, considering the complexity, the concerns, the learning diversities of the students, as well as the challenges regarding the inclusion of the learners in the Young and Adults Education. We’ve intended to investigate how, in the initial formation process, the practices linked to the guidance of the academics in the Supervised Internship discipline of the EJA and in the disciplines of the Young and Adults Education, are contributing to the development of a quality pedagogical work that aims the inclusive process of this category. For this purpose, from a historical analysis of the constitution of education, the first chapter approaches issues such as social rights regarding the formation of citizenship, making effective these rights in social practices that serve as instruments that contribute to the reduction of inequalities and discriminations. The chapter two presents the discussion about the initial formation, the possibility of comprehension of the changes that occurred in the teaching formation process, throughout a reflection about the practice in an integration in the initial teaching formation capable of meeting the present demands of the school reality, that enables more inclusive and better quality educational practices, with a look on the practices of the Pedagogy Course which forms the lecturer to work under a perspective of the diversity regarding the distinctive public found in the EJA turning this category into an inclusive space of achievements and challenges to the professional of education. In the chapter three it is presented the method used throughout the resulting research of the focal group meetings that enables the amplitude on the comprehension of the object of study from the academics reports results of the internship experiences and of the discussions realized in the theoretical disciplines that were subsidized on this stage of formation and the Internship discipline, through an analysis of these reports reflecting on the notes made in light of researches of this field and authors that contribute on the reflection of this process of formation. The conclusion is that the initial formation of the teachers that work with the EJA has been a path that has been built in this Course, more emphasized to specific disciplines but without excluding others, which ends up reverberating on pedagogical practices that don’t consider the context of the adult student, because shallow and rushed discussions if not connected with the reality of this category and its educational practice.